Trophic redundancy in benthic fish food webs increases with scarcity of prey items, in the Southern Baltic Sea - de la Vega, Camille; Paar, Martin; Köhler, Linda; von Dorrien, Christian; Kriegl, Michael; Oesterwind, Daniel; Schubert, Hendrik (Frontiers in Marine Science, 2023)
Bottom trawling is one of the main pressures on benthic ecosystems, directly impacting the targeted species and physically disturbing the seabed and the benthic invertebrate communities, in turn indirectly impacting benthivorous fish and the entire benthic food web structure and functioning. To predict the cascading effect of bottom trawling on benthic and demersal fish communities, it is crucial to understand the trophic interactions between benthic and demersal fish and benthic invertebrates. Here, we assessed the diet of benthic and demersal fish and the structure and functioning of the benthic food web in two areas in the German Baltic Sea, the Fehmarnbelt and the Odra Bank. The Fehmarnbelt benthic invertebrate community is characterized by a high number of species and biomass, contrary to the one on the Odra Bank which is species poor with high individual abundance but low biomass. We used mixing models based on stable isotopes of carbon and nitrogen combined with stomach content analyses to estimate the fish diet at both sites, and we used community-wide trophic indices, derived from stable isotopes to compare the structure and functioning of the fish benthic food webs. We show that fish in the Fehmarnbelt can chose preferential prey items, resulting in higher trophic diversity, contrary to fish on the Odra Bank, which feed on all available prey species, resulting in higher trophic redundancy. We found that the generalist behavior of fish on the Odra Bank is likely the result of scarcity in prey items, the benthic invertebrate community being species poor with high abundance of small individuals. We demonstrate that the differences in structure and functioning of the benthic fish food web between the two sites was mainly driven by differences in the characteristics of the benthic prey communities.